PENGARUH LOKASI TOKO DAN PROMOSI TERHADAP MINAT BELI KONSUMEN PADA DISTRO JENAWI OBLONG RIAU PEKANBARU - Ekawanti, Ulfa; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The research conducted at Distro Jenawi Oblong Riau Pekanbaruwhere located in Jl. Durian No. 2D, Simpang Pepaya, Sukajadi. The problem in this study is number of buyers has decreasing, percentage of target achievement has decreased, and the failure of the company’s sales target has not been achieved, this study aims to determine the effect of store location and promotion on consumer buying interest at Distro Jenawi Oblong Riau Pekanbaru. In this study use quantitive descriptive with SPSS program. The population in this is are consumers at Distro Jenawi Oblong Riau Pekanbaru. The sampling technique chosen is slovin Formula with a sample 86 respondents. Hypothesis testing uses a simple linear analysis method and multiple analysis with result showing that store location and promotion have a positive and significant effect on consumer buying interest at Distro Jenawi Oblong Riau Pekanbaru. With the calculation of the coefficient of determination (R2) store location on consumer buying interest the value of R square is 0,299 or 29,9% and promotion on consumer buying interest the value of R square is 0,278 or 27,8% and coefficient of determination (R2) store location and promotion on consumer buying interest the value of R square is 0,360 or 36%. This show that the location of store and promotion gives an effect of 36% on consumer buying interest at Distro Jenawi Oblong Riau Pekanbaru, while remaining 64% is effected by other variables that aee not examined in this study. Key words: Store Location, Promotion, Consumer Buying Interest